Improving Cloud System Performances by Adopting Nvram-Based Storage Systems - Kim, Jisun; Park, Yunjoo; Nam, Sunhwa A; Choi, Hyunkyoung; Cho, KyungWoon; Bahn, Hyokyung (International Journal of Natural Sciences Research, 2016)
NVRAM is being considered as an additional memory/storage component of future cloud computing systems. This paper investigates how much performance improvement can be obtained if we add NVRAM as the memory/storage media of cloud systems. As NVRAM is put on DDR slots, it is byte-accessible and hence can be used as a memory medium like DRAM. It can also be utilized as swap or journal devices if we use it as a block I/O device. We first consider NVRAM as a storage cache, and then, we measure the performance of systems that additionally use NVRAM as memory, swap, and journal devices. We use two workloads, I/O and memory intensive workloads. Our experiments show that using NVRAM as a journal device performs the best in I/O-intensive workload as it performs journaling I/O on NVRAM instead of slow storage. Using NVRAM as memory or swap devices does not show good results in I/O-intensive workload. However, in case of memory-intensive workload, NVRAM memory significantly improves the performance, and NVRAM swap also gains a certain level of improvement. We expect that our experiments will be helpful in the design of NVRAM-based cloud systems for memory or I/O intensive workload situations.